Ordbog over det norrøne prosasprog Online: struktur og brug - Jóhannsson, Ellert Þór; Battista, Simonetta (Nordiske Studier i Leksikografi, 2018)
The topic of this article is the structure of A Dictionary of Old Norse Prose (ONP) and the use of its online version. This web-based dictionary reflects the complex history of the ONP dictionary project, which has evolved from a traditional print publication to an online version. In this article, we discuss the editorial approach to the material and demonstrate some of the features of ONP Online. We look at various aspects of the online dictionary and consider some of the benefits of this new medium.